Supramolecular-structured hydrogels showing a reversible phase transition by inclusion complexation between poly(ethylene glycol) grafted dextran and alpha-cyclodextrin - Huh, KM; Ooya, T; Lee, WK; Sasaki, S; Kwon, Ick Chan; Jeong, Seo Young; Yui, N (American Chemical Society, 2001)
Supramolecular-structured hydrogels were prepared on basis of the inclusion complexation between poly(ethylene glycol) grafted dextrans and alpha-cyclodextrins (alpha -CDs) in aqueous media. The inclusion complexes from the PEG grafted dextrans showed a unique gel-sol phase transition which cannot be obtained from usual polymer inclusion complexes that form crystalline precipitates. The gel-sol transition was based on the supramolecular assembly and dissociation, and the transition was reversible with hysteresis. The transition temperature was controllable by variation in the polymer concentration and the PEG content in the graft copolymers as well as the stoichiometric ratio between the guest and host molecules. The properties of the hydrogel were characterized by DSC, X-ray diffraction, and C-13 CP/MAS NMR. The X-ray diffraction data indicated that the gel contains a channel-type crystalline structure, demonstrated by a strong reflection at 2 theta = 20 degrees (d = 4.44 Angstrom). It was confirmed from the DSC and C-13 CP/MAS NMR measurements that all the PEG grafts participate in the complexation. A phase-separated structure consisting of hydrophobic and channel-type crystalline PEG inclusion complex domains and hydrated dextran matrices was suggested as the internal structure, which comprises the supramolecular-structured hydrogel.